Code Switching and Code Mixing in UMS Student Speech on Social Media Twitter @UMSfess - Sari, Vira Sukma Permata; Markhamah, M (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study was conducted to analyse the use of code-mixing in Livjunkie’s YouTube content focusing on the types of code-mixing and the factors un-derlying their use. Methodology: This study uses a qualitative descriptive approach, with data sources from tweets from students who follow the auto-based @UMSfess. Data collection was carried out through listening and recording. The data analysis technique used the matching and Determining Elements Sorting (PUP) techniques. Results: The study's results indicate that there are two forms of code-switching: tem-porary code-switching and permanent code-switching. There are two forms of code mixing: word code-mixing and phrase code-mixing. Applications/Originality/Value: The core of this study is to determine the form of code-switching and code-mixing in the speech of students on the auto base tweet @UMSfess and the factors causing the occurrence of code-switching and code-mixing.